PENGARUH MANAJEMEN KONFLIK DAN MANAJEMEN RISIKO TERHADAP EFEKTIVITAS TENAGA KERJA PADA PT “X” - Joonner Rambe (Jurnal Manajemen FE-UB, 2018)
In this study, the influence of conflict management and risk management on work effectiveness in company activities in anticipating risk management in the daily operations of the company is summarized in a number of specific categories. The focus is on increasing employee productivity through improving work effectiveness. In this study used a multiple regression analysis method, in order to get perceptions going forward. The results obtained from multiple regression equations are Y = 20.781 + 0.659 X1 + 0.085 X2, Correlation (R) is 0.828, R Square is 0.686 while the coefficient of determination (Adjusted R Square) from the output of regression statistics in this study is 0.674 , this explains that the contribution given to conflict management variables, and risk management to the effectiveness of the workforce is 67.4% while the remaining 32.6% is influenced by other factors not examined in this study such as organizational climate, commitment, compensation, and others.  Key words: conflict management, risk management, work effectiveness